Quantitative assessment of the cell surface proteome to identify novel therapeutic targets in cholangiocarcinoma. (26th February 2015) - Stephenson, Barney; Shimwell, Neil; Humphreys, Elizabeth; Ward, Douglas; Adams, David; Martin, Ashley; Afford, Simon
Abstract: Background: Cholangiocarcinoma has a high mortality and morbidity. Median survival is less than 6 months. Surgical resection is appropriate in certain circumstances. Because distal cholangiocarcinoma is difficult to distinguish from pancreatic cancers, patients might not receive optimum therapy. Proteomics is the study of complex cellular proteins using mass spectrometry. The aim of this study was to determine the constituent proteins on the cell surface of a model of cholangiocarcinoma. Methods: A sample preparation technique to enrich for cell surface proteins of the intrahepatic cholangiocarcinoma cell line CC-SW-1 was developed by modifying a NeutrAvidin-biotin system. After isolation, trypsin digestion, and purification, peptides were fractionated for tandem mass spectrometry before being analysed with the NCBInr database and the Mascot search algorithm. Results were confirmed by immunohistochemistry using a peroxidase detection technique on paraffin-embedded sections from resected specimens. Findings: Peptide enrichment was confirmed by electrophoresis. 862 proteins were consistently expressed between samples (n=3). 271 of these proteins were attributed only to the cell surface. They included proteins used clinically for staging disease (cytokeratin 19 [CK19]), identifying cancer stem cells (epithelial cell adhesion molecule [EpCAM], neural cell adhesion molecule [NCAM], epithelial growth factor receptor [EGFR]), and indicating potential for differentiation (Frozzled receptor, Notch pathway). Novel markers from the tumour necrosis factor (TNF) receptor superfamily were also identified. Immunohistochemistry confirmed these findings. Interpretation: The results from this surface proteomic profiling could help to identify novel therapeutic targets in cholangiocarcinoma. Further development of this technique could be translated to distinguish between distal cholangiocarcinoma and pancreatic cancers. Funding: UK Medical Research Council.